The epidemiology and risk factors of anal and oropharyngeal human papillomavirus (HPV) in males living with human immunodeficiency virus (HIV): A protocol for systematic review and meta-analysis - Zhang, Mengni; Huang, Yajing; Zhang, Shipeng; Peng, Shunlin (PloS one, 2025)
People living with human immunodeficiency virus (HIV) are more likely to be infected with human papillomavirus (HPV), which can lead to anal and oropharyngeal cancer in males, increasing the complexity of the disease. The aim of this study is to learn more about epidemiological data and factors influencing anal and oropharyngeal HPV infections in males with HIV through a systematic literature review in order to provide evidence for future interventions. The PubMed, Embase, Web of Science, Cochrane Library, PsycINFO, and ClinicalTrials.gov databases will be searched from build to June 2024. Two researchers will independently carry out study selection, data extraction and risk of bias assessment. STATA 16.0 will be used to conduct meta-analysis. The estimated pooled prevalence of anal and oropharyngeal HPV (any HPV, high-risk HPV, low-risk HPV, type-specific HPV, and multiple HPV) in males living with HIV will be presented as percentage prevalence (p * 100%) with corresponding 95% confidence intervals (CI) by DerSimonian-Laird random-effect meta-analyses. Subgroup analysis will carried out by geographic region, income level, race, age, publication year, HPV genotyping, and risk factors (e.g., sexual behavior patterns). Risk factors and interventions-related dichotomous variables or continuous variables will be summarized as odds ratios (OR) and standardized mean differences, and reported through forest plots. The OR (greater than 1) shows an association (correlated). Heterogeneity will be assessed using the I2. Funnel plots, Begg and Egger tests will be applied to detect potential publication bias. CRD42024579641.